PREFERENSI DAN KEMAMPUAN MAKAN TIKUS RUMAH (Rattus–rattus diardii) PADA BEBERAPA VARIETAS BERAS (Oryza sativa L.) DI PENYIMPANAN - -, RAHAYU M; PAKKI, TERRY; SUKMAWATI, TITI (Jurnal Agroteknos, 2014)
This research was conducted in the Laboratory Agrotechnology of the Faculty of Agriculture , University of Halu Oleo Kendari  from June to July 2013. The purpose of this study was to evaluate the preferences and eating ability of rat on some varieties of rice in storage. The sign of study was arranged in latin square design, wich consists of five varieties of treatment that Ciliwung varieties, Konawe varieties, Pandan Wangi varieties, Mekongga varieties and Dolog rice, so that there are 25 experimental units for eating ability of rats hungry and 25 experimental units for the eating ability of rats not hungry, coupled 3 treatment with respective 3 replication for eating preference in order to obtain 59 experimental units. Were analyzed using analysis of variance, followed by Duncan’s Multiple Range Test (DMRT). The results showed that eating preferences with the treatment option on the five varieties obtained preferred of rats with an average consumption respectively are Pandan Wangi varieties 6.82 g tail -1. Eating ability of rats showed all the tested varieties pferred to rats except Dolog rice, so ii may be recomendation to use Pandan Wangi varieties or Konawe varieties as varieties trap or pulling varieties  for avoid major varieties of rat infestation.